Effect of ketone monoester supplementation on elite operators’ mountaineering training - Miyatsu, Toshiya; McAdam, Jeremy; Coleman, Kody; Chappe, Ed; Tuggle, Steven C.; McClure, Tyler; Bamman, Marcas M. (Frontiers in Physiology, 2024)
Special Operations Forces (SOF) often conduct operations in physiologically stressful environments such as severe heat, cold or hypoxia that can induce declines in a variety of cognitive abilities. Given promising empirical demonstration of exogenous ketone monoester (KME) supplementation's efficacy in attenuating cognitive performance decline during hypoxia at rest in a laboratory setting, we conducted a real-world, field experiment examining KME's efficacy during high-altitude mountaineering, an austere environment in which US SOF have conducted increasing numbers of operations over the past two decades. Specifically, 34 students and cadre at the U.S. Army 10 th Special Forces Group Special Operations Advanced Mountaineering School (SOAMS) participated in a randomized, double-blind, placebo (PLA)-controlled cross-over trial (KME vs. PLA) over 2 days of tactical mountain operations training. The participants ascended from 7,500 ft in altitude (basecamp) to 12,460 ft one day and 13,627 ft the other day (in randomized order) while performing various training activities inducing high physical and cognitive loads over 8-12 hours, and consumed 6 doses of KME or PLA 2 to 3 hours apart throughout each training day. While KME increased blood ketone levels and decreased glucose levels, there were no clear indications that the elevated ketone level brought physical or cognitive performance enhancement. KME also produced greater incidence of heartburn, nausea, and vomiting. In these elite operators, high altitude mountaineering had limited impact on cognitive performance and KME supplementation did not demonstrate benefit.